Members of co-operative perception toward services provided by Koperasi Serbaguna Kakitangan Majlis Perbandaran Kuantan Berhad (KOSPEK MPK BERHAD) / Masnieaida Mohd Nazir - Mohd Nazir, Masnieaida (Faculty of Business and Management, 2005)
The purpose of this research is to study on members of Co-operative perception toward services provided by KOSPEK MPK Berhad. This research is also to study evaluates the effectiveness of method efforts by KOSPEK MPK Berhad. Besides that it is also to study from their members of Co-operative opinion for the most effective method of services. So that, KOSPEK MPK Berhad can be compare their products and services based on the members of Co-operative view. For the purpose of this study the exploratory and descriptive research was used. Convenience sampling size has been utilized with 100 respondents as the sample size and then chooses the member of 20 workers in each department and five departments that will be selected as a fundamental of the study. This is because the majority of the Co-operative's members that used the products and services are come from Car Parks Department, Parks and Recreation Department, Mechanical Engineering and Electrical Department, Maintenance Department and Enforcement and Security Department in Kuantan Municipal Council. Questionnaires were distributed as the survey instrument; besides conducting interviewing as the source of primary data other reliable resources would serve as secondary. The data will interpret by using the SPSS program and the result of the reliability testing that has been done for this research is 0.871, it included in the rank of 0.8 - 0.9 meaning that the data obtained from this research is considered as very good.